Placing Salt/Soy Sauce at Dining Tables and Out-Of-Home Behavior Are Related to Urinary Sodium Excretion in Japanese Secondary School Students - Okuda, Masayuki (Nutrients, 2017)
We investigated whether home environment, salt knowledge, and salt-use behavior were associated with urinary sodium (Na) excretion in Japanese secondary school students. Students (267; mean age, 14.2 years) from Suo-Oshima, Japan, collected three overnight urine samples and completed a salt environment/knowledge/behavior questionnaire. A subset of students (n = 66) collected, on non-consecutive days, two 24 h urine samples, and this subset was used to derive a formula for estimating 24 h Na excretion. Generalized linear models were used to examine the association between salt environment/knowledge/behavior and Na excretions. Students that had salt or soy sauce placed on the dining table during meals excreted more Na than those that did not (p(for trend) < 0.05). A number of foods to which the students added seasonings were positively associated with Na excretion (p(for trend) = 0.005). The students who frequently bought foods at convenience stores or visited restaurants excreted more Na in urine than those who seldom bought foods (p(for trend) < 0.05). Knowledge about salt or discretionary seasoning use was not significantly associated with Na excretion. The associations found in this study indicate that home environment and salt-use behavior may be a target for a public health intervention to reduce salt intake of secondary school students.